An illustration of speech articulation impairment in children with cerebral palsy tested by the Goldman-Fristoe method - Rusmarini, Ade Pungky; Haroen, Edeh Rolleta; Indriyanti, Ratna (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
Seventy percent of children with cerebral palsy were found to suffer from speech articulation impairment. The purpose of this research was to obtain an illustration of speech articulation impairÂment in children with cerebral palsy tested by the Goldman-Fristoe method at the SLB-D School for DisÂabled Children Bandung in 2007. This was a descriptive research. Sampling was carried out by purposive sampling. The speech articulation impairment test was carried out on the basis of the Goldman-Fristoe method, that is, an articulation test which places the consonant at the beginning, middle, and at the end of a word, to test speech articulation impairment in children with cerebral palsy. Research results indicated that speech articulation impairment in the bilabial consonants /p/,/b/, and /m/ is the average 85.51%. Speech articulation impairment of the labiodental consonants /f/ and /v/ is an average 89.13%. Speech articulation impairment of the alveolar or dental consonants /t/ and /d/ is an average of 80.43%. Speech articulation impairment in the palatal consonants /c/ is an average of 82.60%. Speech articulation impairment in velar consonants /k/ and glottal consonants /h/ is an average of 86.96%. ReÂsearch results indicated that more than three-fourths of children with cerebral palsy at the SLB-D School for Disabled Children Bandung in 2007 suffered from speech articulation impairment.